THE IMPLEMENTATION OF CASHLESS PAYMENT SYSTEM IN THE MSMES SECTOR IN THE PERSPECTIVE OF ISLAMIC ECONOMICS TO ENCOURAGE THE DEVELOPMENT OF THE DIGITAL ECONOMY (CASE STUDY OF POSBLOC MEDAN CITY) - Zalika Fauja; Muhammad Lathief Ilhamy Nasution; Budi Dharma (Universitas Islam Negeri Mataram, 2023)
The development of the digital economy presents new, increasingly diverse financial service products. One of them is non-cash payments or cashless payments, which are the latest innovations and are increasingly prevalent in buying and selling payments to MSMEs. This study aims to find out how the Cashless system is implemented in the MSME sector in the city of Medan, then to find out how the Islamic economic perspective is in implementing the Cashless payment system. This study uses a qualitative research method with data collection techniques, namely by observation, interviews, documentation on the UMKM posbloc in Medan city as well as a study of the literature to be analyzed with the author's observations to answer the formulation of the problem on this problem. The results of this study show that the Cashless system used by the Medan city posbloc is in several ways, namely debit cards, credit cards or by scanning the QRIS code (Quick Response Code Indonesian Standard). APMK (Payment using a card) or with a QRIS scan which has been promoted by Bank Indonesia provides convenience in making transactions with a cashless system without cash more efficiently and effectively. According to the Islamic economic perspective, QRIS is permissible because there is no usury in buying and selling payments to MSMEs. However, there are still a number of obstacles in the implementation of the cashless posbloc payment system in Medan city, one of which is the internet which is not stable enough, and the lack of outreach.